State estimation of lithium-ion battery for shipboard applications: Key challenges and future trends - Laiqiang Kong; Yingbing Luo; Sidun Fang; Tao Niu; Guanhong Chen; Lijun Yang; Ruijin Liao (Green Energy and Intelligent Transportation, 2025)
With the aggravation of environmental problems caused by the long-term dependence of shipping traffic on heavy fossil fuels, it is an irreversible development trend for electrified ships to integrate large-capacity battery energy storage systems (ESSs). As the main component, the shipboard lithium-ion battery (LIB) plays an important role in the operation of ship power system to balance the source and load sides. By analyzing the effects of temperature, vibration, humidity and salt spray on battery characteristics in the shipping environment, this paper points out that the characteristics of shipboard LIB have certain differences on the state changes with the land-based batteries. Then, this paper systematically reviews the most commonly used LIB modeling and state estimation methods and their applicability to the shipping environment, including the empirical models, electrochemical models, equivalent circuit models (ECMs) and data-driven models. On this basis, the state estimation methods of state of charge (SOC), state of power (SOP), state of health (SOH), state of energy (SOE) and state of temperature (SOT) are reviewed. Finally, the challenges and prospects of shipboard LIB research are prospected, in the hope of providing inspiration for the development and design of efficient and safe electric ships.